First record of Dichotomaria obtusata (Ellis & Solander) Lamarck (Nemaliales, Rhodophyta) in the Mediterranean Sea - HOFFMAN, R.; LIU, S.-L.; LIPKIN, Y.; STERNBERG, M. (Mediterranean Marine Science, 2015)
Global climate change is causing the Mediterranean coastal area of Israel to gradually acquire tropical characteristics. Rising sea surface temperatures in the eastern Mediterranean basin have facilitated the introduction, settlement and establishment of hundreds of alien species (Zenetos et al. 2012). The vast majority of these exotic species are of Indo-Pacific origin. We report the occurrence of the genus Dichotomaria in the eastern Mediterranean on the basis of specimens identified as Dichotomaria cf. obtusata (J. Ellis & Solander) Lamarck. Tetrasporophytes with sporangial initials were identified morphologically and confirmed molecularly using plastid rbcL sequences. We also discuss possible paths of introduction of this and other alien species into the Levantine Sea.